Effectiveness of DR-TA Strategy with Interactive Multimedia on Thai Reading Comprehension Ability among Grade 3 Students in a Bilingual School - Thawornsuth, Rattima; Visuttakul, Chidchamai (Al-HIKMAH Journal, 2024)
The objectives of this research article were 1) to develop and assess the effectiveness of interactive multimedia in enhancing Thai reading comprehension ability for grade 3 students, based on the 80/80 criteria; 2) to compare the reading comprehension ability of grade 3 students before and after learning through the DR-TA strategy with interactive multimedia; and 3) to investigate the satisfaction levels of grade 3 students towards learning through the DR-TA strategy with interactive multimedia. The sample consisted of grade 3 students attending a bilingual school in Bangkok, comprising one classroom with twenty-five students. The research instruments included 1) eight interactive multimedia lessons, 2) four Thai lesson plans, 3) a reading comprehension test comprising 20 multiple-choice questions, and 4) a satisfaction questionnaire consisting of 10 items. The statistics used in data analysis were the mean, standard deviation, Kolmogorov-Smirnov Test and t-test for dependent samples. The findings revealed that 1) interactive multimedia proved to be effective based on established standards (89/90); 2) students exhibited higher post-learning reading comprehension ability compared to pre-learning levels, with statistical significance at the 0.05 level; and 3) students expressed the highest level of satisfaction ( =4.90, S.D.=0.27).